A Comparative Analysis of the English-Spanish War: Exploring Naval Strategies, Diplomatic Relations, and Socioeconomic Impacts in the 16th Century - Delfina Girasol (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
This research paper presents a comprehensive analysis of the English-Spanish War that took place during the 16th century. The study examines the naval strategies employed by both sides, the diplomatic relations that influenced the conflict, and the socioeconomic impacts that resulted from the war. By analyzing primary sources and scholarly works, this research aims to provide a deeper understanding of the factors that shaped the course and outcome of the English-Spanish War. The study contributes to existing historical scholarship by offering a comparative perspective on the conflict and shedding light on its significance in shaping European history